DETERMINANTS OF EFFICIENCY OF NON-LIFE INSURANCE COMPANIES: EVIDENCE FROM VIETNAM - Лінь ДТ Трінь (Фінансово-кредитна діяльність: проблеми теорії та практики)
Insurance companies play a major role in the financial systems of countries. However, studies on the efficiency and factors affecting the efficiency of insurance companies in Vietnam are still very limited. The purpose of the paper is to explore the efficiency and determinants of efficiency of non-life insurance companies operating in Vietnam. The author applies methods such as descriptive statistics, data envelopment analysis (DEA) and Tobit regression. The results show that the mean efficiency of non-life insurance companies operating in Vietnam during the research period is 0.806, the highest mean efficiency is 1.0 and the lowest is 0.303. Also, domestic insurance companies have the highest mean efficiency of 0.855, while joint venture insurers and foreign insurers have lower efficiency with a mean efficiency of 0.739 and 0.728. The research results also show that equity, debt-to-asset ratio, the ratio of operating expenses to assets, ROE, ROA, foreign capital to total capital ratio and annual GDP growth rate affect the efficiency of non-life insurance companies in Vietnam.